Reviews on drag reducing polymers - Tiong, A.; Kumar, P.; Saptoro, Agus (2015)
Polymers are effective drag reducers owing to their ability to suppress the formation of turbulent eddies at low concentrations. Existing drag reduction methods can be generally classified into additive and non-additive techniques. The polymer additive based method is categorized under additive techniques. Other drag reducing additives are fibers and surfactants. Non-additive techniques are associated with the applications of different types of surfaces: riblets, dimples, oscillating walls, compliant surfaces and microbubbles. This review focuses on experimental and computational fluid dynamics (CFD) modeling studies on polymer-induced drag reduction in turbulent regimes. Other drag reduction methods are briefly addressed and compared to polymer-induced drag reduction. This paper also reports on the effects of polymer additives on the heat transfer performances in laminar regime. Knowledge gaps and potential research areas are identified. It is envisaged that polymer additives may be a promising solution in addressing the current limitations of nanofluid heat transfer applications.